2018
DOI: 10.1097/gox.0000000000001933
|View full text |Cite
|
Sign up to set email alerts
|

Scratch Collapse Test for Carpal Tunnel Syndrome: A Systematic Review and Meta-analysis

Abstract: Background:Despite the fact that carpal tunnel syndrome (CTS) is the most common entrapment neuropathy, the diagnostic accuracy of clinical screening examinations for CTS is controversial. The scratch collapse test (SCT) is a novel test that may be of diagnostic advantage. The purpose of our study was to determine the diagnostic accuracy of the SCT for CTS.Methods:A literature search was performed using PubMed (1966 to April 2018); Ovid MEDLINE (1966 to April 2018); EMBASE (1988 to April 2018); and Cochrane Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…27 28 Multiple reports have challenged the proposed mechanism of action utilized by SCT—the cutaneous silent period (CuSP). 28 The CuSP is described as a transient decrease in EMG activity observed after a noxious stimulus of a nerve. 28 Some studies have shown that the CuSP was prolonged in moderate CTS patients, but absent in severe CTS patients.…”
Section: Resultsmentioning
confidence: 99%
“…27 28 Multiple reports have challenged the proposed mechanism of action utilized by SCT—the cutaneous silent period (CuSP). 28 The CuSP is described as a transient decrease in EMG activity observed after a noxious stimulus of a nerve. 28 Some studies have shown that the CuSP was prolonged in moderate CTS patients, but absent in severe CTS patients.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies on the application of SCT for the diagnosis pf CTS, Cheng et al (16) reported a sensitivity and specificity of 0.69 and 0.99 in 228 cases, Gillenwater et al (21) reported 0.77 and 0.99 in 24 cases, Huynh et al (22) performed a meta-analysis of Blok et al (23), Makanji et al (24) and Simon (25) et al who reported a sensitivity and specificity of 0.32 and 1.00 in 37 cases, 0.34 and 0.61 in 88 cases, and 0.28 and 0.38 in 40 cases, respectively . The sensitivity and specificity reported by Montgomery et al (26) were 0.07-0.15 and 0.78-0.87 in 92 cases, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…trained with Dr. Mackinnon, the original promoter of the scratch collapse test and senior author of the 2008 article by Cheng et al 23 The learning curve in performing the scratch collapse test has been recognized in several studies, but given our examiner's prior experience and frequent application of the test in practice, it likely played an important role in our results. [5][6][7]23,26 When performing the scratch collapse test, the examiner should be thoroughly versed in nerve topographic anatomy and common areas of nerve compression, as inaccurate or wide cutaneous stimulation could lead to varying results. [3][4][5]7 This idea is supported by the positive results reported by the original senior author for peroneal nerve compression, and the wide range of sensitivities when performed by novice examiners.…”
Section: Discussionmentioning
confidence: 99%